2017
DOI: 10.1039/c6cc09952a
|View full text |Cite
|
Sign up to set email alerts
|

3R phase of MoS2 and WS2 outperforms the corresponding 2H phase for hydrogen evolution

Abstract: Herein, we compare the bulk, 2H and 3R phases of two most prevalent TMD materials: MoS and WS. The 3R phase outperforms its 2H phase counterpart in hydrogen evolution reaction catalysis and is even comparable with the exfoliated, 1T phase in the case of MoS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
152
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(167 citation statements)
references
References 27 publications
3
152
0
Order By: Relevance
“…Recently,atargeted synthesis method for preparing stable 2H-and 1T-MoS 2 monolayers by al ithium moltens alt approachwas also reported. [17] The different exposure of S-edges significantly alters the (electro)catalytic and optical properties of the materiala nd the same stands true for the density of defects along the lat-tice. Markedly, annealing of the 1T phase gradually restores the 2H one, resulting in an enhancement of the photoluminescence of the nanosheets, which can be employed as fingerprint for the restorationo ft he semiconductingproperties.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently,atargeted synthesis method for preparing stable 2H-and 1T-MoS 2 monolayers by al ithium moltens alt approachwas also reported. [17] The different exposure of S-edges significantly alters the (electro)catalytic and optical properties of the materiala nd the same stands true for the density of defects along the lat-tice. Markedly, annealing of the 1T phase gradually restores the 2H one, resulting in an enhancement of the photoluminescence of the nanosheets, which can be employed as fingerprint for the restorationo ft he semiconductingproperties.…”
Section: Introductionmentioning
confidence: 96%
“…[16] Besides the polytypew ith 2H symmetry,t he 3R rhombohedral one is also a semiconducting phase and recently it was reported that it is possible to regulate the 2H/3R ratio by monitoring the temperature during the bottom-up synthesis of monolayered nanosheets. [17] The different exposure of S-edges significantly alters the (electro)catalytic and optical properties of the materiala nd the same stands true for the density of defects along the lat-tice. [18] Moreover atmosphericf actorss uch as air and humidity shouldalso be considered, as adsorbed oxygen and water moleculesc an accept electrons, thus reducing trion emission in intrinsically doped TMDs and leading to an enhanced emission from excitons.…”
Section: Introductionmentioning
confidence: 99%
“…Note: anatase (A), rutile (R), brookite (B), amorphous (Am), polymorphic (Poly), cubic (C), trigonal (Trig), hexagonal (Hex), orthorhombic (Or), tetragonal (Tet), rhombohedral (Rho), monoclinic scheelite (MonS), tetragonal zircon (TetZ), tetragonal Scheelite (TetS), monoclinic (Mon), triclinic (Tri), Ruddlesden–Popper phases (RPP), kesterite (K), stannite (S), and primitive mixed CuAu (PMCA). Data for (b) have been collected from published articles to date . and we include the phase(s) for the periodic elements that show at least one phase for the above redox reactions.…”
Section: Spe For Redox Processesmentioning
confidence: 99%
“…Data for (b) have been collected from published articles to date. [2,[45][46][47][48][49] and we include the phase(s) for the periodic elements that show at least one phase for the above redox reactions.…”
Section: Catalytic Activities Induced By Spementioning
confidence: 99%
“…Models of Nanofilms : Different symmetry polymorphs for WS 2 bulk are mentioned in the literature: metastable metallic hexagonal P3¯m1 (space group Nr 164) 1 T phase (in some sources this phase is classiffied as tetragonal), the most stable P 6 3 / mmc (space group Nr 194) hexagonal 2 H phase as well as metastable Rtrue3¯m (space group Nr 160) 3 R rhombohedral phase exhibiting semiconducting behavior . Nomenclature of phases (1 T , 2 H , 3 R ) shows a number of triple plane S‐W‐S atomic layers in the corresponding primitive unit cell.…”
Section: Van Der Waals Interaction Influence On Structural and Electrmentioning
confidence: 99%